Analisis Kesejahteraan Masyarakat Pasca Pemekaran Daerah: Studi Kasus Kabupaten Morowali Utara - Umar Dahalu (PENA BANGSA: Bisnis dan Tata Kelola Publik Adaptif, 2025)
Regional expansion is a decentralization strategy intended to improve community welfare through accelerated public service delivery, enhanced development capacity, and more equitable access to resources. North Morowali Regency, as a newly created administrative region, demonstrates dynamic development patterns that merit examination, particularly concerning local government performance in the health, education, economic, and infrastructure sectors. This study aims to assess the extent to which regional expansion has contributed to improving community welfare in North Morowali by analyzing development achievement data presented in official government documents. The results indicate that the local government has successfully expanded access to health services through Universal Health Coverage, the construction of a Pratama Hospital, increased ratios of health workers, and free healthcare services. In the education sector, improved access, the provision of digital facilities, and free education policies have contributed to strengthening human capital. In the economic sector, the creation of 20,000 jobs, capital assistance programs for youth and women, and infrastructure development reflect progressive growth. The study concludes that, following regional expansion, North Morowali has experienced significant improvements in essential public services; however, challenges related to budget sustainability, human resource quality, and equitable development across regions still require further strengthening.